Cardiac manifestations of MIS-C: cardiac magnetic resonance and speckle-tracking data - Scarduelli, Lorenzo; De Guillebon De Resnes, Jean-Marie; Ducreux, Dorothée; Bernardor, Julie; Afanetti, Mickael; Dupont, Audrey; Barthelemy, Sébastien; Gondon, Emmanuelle; Leporati, Julien; Giovannini-Chami, Lisa; Moceri, Pamela (Frontiers in Cardiovascular Medicine, 2023)
Background : Cardiac involvement is central in MIS-C and represents the main cause of morbidity. In this study, we aimed to assess the myocardial damage in patients with MIS-C using cardiac magnetic resonance (CMR) during the acute phase as well as left ventricular and atrial longitudinal strain on admission, at discharge and after 3-months.We performed a single-center prospective cohort and case-control study. Between September 2020 and February 2022, we included 39 patients hospitalized for MIS-C in our center. We performed left ventricular and atrial longitudinal 2D strain analysis on admission and during follow-up; echocardiographic data were compared to a matched control population.Patients above 4 years old with increased troponin underwent CMR.Of 24 patients (mean age 8.2 ± 4.9 years) who underwent CMR, 14 (58%) presented myocardial edema and 6 (25%) late gadolinium enhancement (LGE). LGE was associated with older age (p<0.01), increased BMI (p=0.03), increased ferritin levels (p<0.001), lower left ventricular (LV) ejection fraction (p<0.001), LV longitudinal strain (p=0.004) and left atrial (LA) strain (p=0.05) and prolonged hospital stay (p=0.02). On admission, LV ejection fraction, LV longitudinal and LA strain were impaired and improved gradually over time, LVEF being the fastest to recover while global LV longitudinal strain was still impaired as compared to controls after 3-months (p=0.01).Our study demonstrates that myocardial injury is present in 1/4 th of MIS-C patients and impaired LA and LV myocardial deformation persists at least several weeks after the acute phase. CMR and LV/LA strain could help us individualize MIS-C patients' follow-up.